2020
DOI: 10.3791/59204
|View full text |Cite
|
Sign up to set email alerts
|

Updated Technique for Reliable, Easy, and Tolerated Transcranial Electrical Stimulation Including Transcranial Direct Current Stimulation

Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive method of neuromodulation using low-intensity direct electrical currents. This method of brain stimulation presents several potential advantages compared to other techniques, as it is noninvasive, cost-effective, broadly deployable, and well-tolerated provided proper equipment and protocols are administered. Even though tDCS is apparently simple to perform, correct administration of the tDCS session, especially the electrode positioning and prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Bifrontal protocols would position the anode over F2, and cathode over the F4 scalp position (10–20 EEG System) or in the bifrontal “OLE” montage which can optimize current delivery to DLPFC ( 11 13 ). Targeted tDCS of DLPFC can be achieved using 4x1-tDCS centered over DLPFC ( 142 , 143 ). High-frequency rTMS protocols would target the left DLPFC with 10 Hz, trains of 50 pulses, with intertrain intervals of 25–50 s, at 90–120% of the resting motor threshold, until 3,000 pulses per session, with figure-of-eight coils positioned at the F3 scalp position or using neuronavigation ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bifrontal protocols would position the anode over F2, and cathode over the F4 scalp position (10–20 EEG System) or in the bifrontal “OLE” montage which can optimize current delivery to DLPFC ( 11 13 ). Targeted tDCS of DLPFC can be achieved using 4x1-tDCS centered over DLPFC ( 142 , 143 ). High-frequency rTMS protocols would target the left DLPFC with 10 Hz, trains of 50 pulses, with intertrain intervals of 25–50 s, at 90–120% of the resting motor threshold, until 3,000 pulses per session, with figure-of-eight coils positioned at the F3 scalp position or using neuronavigation ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that tDCS may be used with the anode positioned at the T3 scalp position, and cathode at the T4 scalp position, with 2 mA for 20 min, using 5 × 5 cm or 5 × 7 cm electrodes, together with exercises directed to respiratory function. For targeted temporal cortex tDCS the 4x1 HD-tDCS can be used ( 142 , 143 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined in case examples (Sections 8.1, 8.2), for those centers already engaged in remote supervised tDCS, strategic and incremental protocols changes allow continuation (and even expansion) of protocols. For those centers exploring transition of in-center tDCS to remotely supervised tDCS, there are well-established principles under the Remote Supervised rubric that allow homebased tDCS with compromising reproducibility [46] and detailed supporting documentation [45,56,65,66].…”
Section: Tele-neuromodulation (In Home)mentioning
confidence: 99%
“…It is hypothesized that TES could interfere with slow oscillation in the brain, which could increase the slow wave activity and enhance the lowfrequency electroencephalogram (EEG) activity (i.e., a marker of arousal) (23)(24)(25). Due to its portable features and convenience to use, TES is suitable for self-administration at home (26,27). However, TES is not free of limitations, and it has been criticized for poor spatial accuracy (28).…”
Section: Introductionmentioning
confidence: 99%